The Clinical and Metabolic Effects of Intragastric Balloon on Morbid Obesity and Its Related Comorbidities - Joon Hyun Cho; Mohammad Bilal; Min Cheol Kim; Jonah Cohen (Korean Society of Gastrointestinal Endoscopy, 2021)
Obesity is becoming increasingly prevalent worldwide, and its metabolic sequelae lead to a significant burden on healthcare resources. Options for the management of obesity include lifestyle modification, pharmacological treatment, surgery, and endoscopic bariatric therapies (EBTs). Among these, EBTs are more effective than diet and lifestyle modification and are less invasive than bariatric surgery. In recent years, there have been significant advances in technologies pertaining to EBTs. Of all the available EBTs, there is a significant amount of clinical experience and published data regarding intragastric balloons (IGBs) because of their comparatively long development period. Currently, the United States Food and Drug Administration (FDA) has approved three IGBs, including Orbera (Apollo Endosurgery, Austin, TX, USA), ReShape Duo (ReShape Medical, San Clemente, CA, USA), and Obalon (Obalon Therapeutics, Carlsbad, CA, USA). The aim of this review is to summarize the available literature on the efficacy of IGBs in weight loss and their impact on obesity-related metabolic diseases.